Queers with Guns? Against the LGBT Grain. (February 2022) - Combs, Thatcher Phoenix
Sociological literature on gun ownership in the United States has primarily centered on white, heterosexual, cisgender men and vulnerability to violence. However, many gun owners do not fit this profile. In this article, I begin to fill this gap by focusing on one group—lesbian, gay, bisexual, transgender, and queer (LGBTQ) people—and answer the question: How does the status of being a vulnerable gender and/or sexual minority shape LGBTQ gun owners' perspectives on gun ownership? To do so, I focus on gun literature, LGBTQ lives, and questions of vulnerability, and draw on in-depth interviews with 30 LGBTQ gun owners from across the United States. In this study, LGBTQ gun owners highlight two major themes. First, they discuss how their gender expression/sexuality creates possibilities for violence. Second, they relate minority oppression with the violent uprisings that created the LGBT movement. As such, these LGBTQ gun owners go against the LGBT movement's discourse of pro-gun control and structural change.